Odpowiedzi

2010-04-17T13:06:21+02:00
A=b+c
c=a-b
b=a-c

a=bc+d |-bc
d=a-bc
c=(a-d):b
b=(a-d):c

a=bc-d
c=(a+d):b
b=(a+d):c
d=-a+bc

a=b(c+d)
b=a:(c+d)
c=(a-bd):b
d=(a-bc):b

a=b+c:d
b=a-c:d
c=(a-b)*d
d=(a-b)*(-c)

a=b-c:d
b=a+c:d
c=-a+b*d
d=-a+b*c

a=b:(c+d)
b=a*(c+d)
c=b:a-d
d=b:a-c

a=b:(c-d)
b=a*(c-d)
c=b*a+d
d=b*a+c


a=b:c+d
d=a-b:c
c=b+d*a
b=a-d*c

G=1:R
R=1:G

B=1:K
K=1:B

I=U:R
U=I*R
R=R:I

p=F:S
F=p*S
S=p:F

d=m:V
m=d*V
V=m:d

Q=mG
m=Q:G
G=Q:m

V=Ph
P=V:h
h=V:P

P=UI
U=P:I
I=P:U

c=5R:2M
R=c*2M:5
M=5R:c:2

c=7:2razyR:M
R=c*7*M:2
M=2R:c:7

c=4razyR:M
R=c*M:4
M=4R:c

c=Nrazy34:M
M=c:N34
N=c:N:34